2019
DOI: 10.1002/jgm.3116
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the dual‐faced effects of miR‐141 with chitosan/miR‐141 nanoplexes in breast cancer cells

Abstract: Background miR‐141, known as a tumor suppressive microRNA, is downregulated in breast cancer. However, recent contrasting studies report that it also acts as oncogene when it is upregulated. The present study aimed to investigate whether miR‐141 is a tumor suppressor or oncogenic when it reaches normal levels in chitosan/miR‐141 nanoplexes. Methods Chitosan nanoplexes were prepared using simple complexation method. Nanoplexes were characterized by a gel retardation assay and zeta potential and particle size me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…They also found that treatment with chitosan/miR‐141 nanoplexes significantly reduced the production of VEGF in these cells. However, chitosan/miR‐141 nanoplexes increased the expression levels of two metastatic factors, Tinagl1 and Igfbp‐4, in the BC cells and thus the role of miR-141 in the angiogenesis needs further investigation [84] . MiR-141 suppressed IL-8 and CXCL1 in basal-like BC which led to reduction in tumor growth and MVD [85] .…”
Section: Pro-angiogenic and Anti-angiogenic Mirnas In Bcmentioning
confidence: 99%
“…They also found that treatment with chitosan/miR‐141 nanoplexes significantly reduced the production of VEGF in these cells. However, chitosan/miR‐141 nanoplexes increased the expression levels of two metastatic factors, Tinagl1 and Igfbp‐4, in the BC cells and thus the role of miR-141 in the angiogenesis needs further investigation [84] . MiR-141 suppressed IL-8 and CXCL1 in basal-like BC which led to reduction in tumor growth and MVD [85] .…”
Section: Pro-angiogenic and Anti-angiogenic Mirnas In Bcmentioning
confidence: 99%
“…To overcome these issues, approaches like introduction of chemical modifications or loading siRNA into delivery vectors have been developed [ 19 , 59 ]. Previously, we used chitosan as a delivery vector to repress posttranscriptional vascular endothelial growth factor (VEGF) and zinc finger E-box binding homeobox (ZEB) expression, which resulted in inhibition of tumor angiogenesis and epithelial-mesenchymal transition (EMT) of breast cancer cells [ 60 , 61 , 62 ]. Even though chitosan has low cytotoxic, low bio-persistence, and mucoadhesive properties, weakness in intracellular dissociation and tumor cell specific targeting are still challenging problems, which reflects the necessity for improved delivery systems [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following the same trend, all studies were conducted on molar masses of CS ranging from 20-200 kDa to form intact biologically active nanoplexes [24,25,[36][37][38][39][40][41][42][43]. Exceptionally, few teams compared different molar masses in the same study, which gives more standardized results.…”
Section: Effect Of Chitosan Molar Mass On Nanoplexes (Chitosan Mirna ...mentioning
confidence: 99%
“…As demonstrated in Table 3 and Figure 10, CS miRNA NPs have been investigated mainly for cancer therapy [24,26,27,[33][34][35]37,41,42,53,56,[63][64][65][66][67][68]. Not only can that be attributed to the great characteristics of CS as a natural biocompatible biodegradable modifiable drug delivery system, but CS also has its own biological activities per se [4,92].…”
Section: Cancermentioning
confidence: 99%